O papel das terras privadas sobre a conservação das áreas protegidas dos cerrados, a savana neotropical - Leite, Leandro Henrique (2021)
This work aims to verify the existence of a relationship between variables intrinsic to declared rural properties (proportion of coverage and number of properties), conservation units (area, jurisdiction, location, expropriation) and the occurrence of deforestation. For this, the manipulation of public geographic databases was used to obtain the variables that make up the study. The work covered the entire extension of the Cerrado, one of the world's hotspots, threatened due to the expansion of human activities. The results show the relevance of land tenure and dominance in combating deforestation, allowing the identification of categories and the location of conservation units that have the greatest potential for negative pressure in the future.